Biomechanics of T Cell Dysfunctions in Chronic Diseases - Gunasinghe, Sachith D.; Peres, Newton G.; Goyette, Jesse; Gaus, Katharina (Frontiers in Immunology, 2021)
Understanding the mechanisms behind T cell dysfunctions during chronic diseases is critical in developing effective immunotherapies. As demonstrated by several animal models and human studies, T cell dysfunctions are induced during chronic diseases, spanning from infections to cancer. Although factors governing the onset and the extent of the functional impairment of T cells can differ during infections and cancer, most dysfunctional phenotypes share common phenotypic traits in their immune receptor and biophysical landscape. Through the latest developments in biophysical techniques applied to explore cell membrane and receptor-ligand dynamics, we are able to dissect and gain further insights into the driving mechanisms behind T cell dysfunctions. These insights may prove useful in developing immunotherapies aimed at reinvigorating our immune system to fight off infections and malignancies more effectively. The recent success with checkpoint inhibitors in treating cancer opens new avenues to develop more effective, targeted immunotherapies. Here, we highlight the studies focused on the transformation of the biophysical landscape during infections and cancer, and how T cell biomechanics shaped the immunopathology associated with chronic diseases.